Old heart [large type] - Ferry, Peter (Center Point Large Print, 2016)
"Tom Johnson has just turned eighty-five. When faced with a nursing home, he escapes to the Netherlands to find the woman he fell in love with during World War II. His children want him back, but Tom fights to stay in the Netherlands for love, family and all the remaining rights of an old man"--